Pengaruh Pandemic Covid 19 terhadap Net Performing Financing Bank Pembiayaan Syariah di Indonesia - Maria Indriyani Hewe Tiwu; Yohana Febiani Angi (OECONOMICUS Journal of Economics, 2021)
This study aims to analyze the effect of the Covid 19 pandemic on NPF BPR Sharia during the study period from January 2017 to July 2019. The analytical method used is multiple regression with the COVID-19 pandemic as a dummy variable. The results of this study indicate that the Covid 19 pandemic has no significant effect on the Net Performing Finance of Islamic BPRs during the study period. Islamic BPRs apply sharia principles, namely the provision of funds or bills that are equalized to the results in mudharabah, istishna, murabahah and musyarakah, so that the impact of the Covid pandemic does not have a significant effect on the NPF of Islamic BPRs